Advances in CO2 utilization employing anisotropic nanomaterials as catalysts: a review - Kandathil, Vishal; Manoj, Narayanapillai (Frontiers in Chemistry, 2023)
Anisotropic nanomaterials are materials with structures and properties that vary depending on the direction in which they are measured. Unlike isotropic materials, which exhibit uniform physical properties in all directions, anisotropic materials have different mechanical, electrical, thermal, and optical properties in different directions. Examples of anisotropic nanomaterials include nanocubes, nanowires, nanorods, nanoprisms, nanostars, and so on. These materials have unique properties that make them useful in a variety of applications, such as electronics, energy storage, catalysis, and biomedical engineering. One of the key advantages of anisotropic nanomaterials is their high aspect ratio, which refers to the ratio of their length to their width, which can enhance their mechanical and electrical properties, making them suitable for use in nanocomposites and other nanoscale applications. However, the anisotropic nature of these materials also presents challenges in their synthesis and processing. For example, it can be difficult to align the nanostructures in a specific direction to impart modulation of a specific property. Despite these challenges, research into anisotropic nanomaterials continues to grow, and scientists are working to develop new synthesis methods and processing techniques to unlock their full potential. Utilization of carbon dioxide (CO2) as a renewable and sustainable source of carbon has been a topic of increasing interest due to its impact on reducing the level of greenhouse gas emissions. Anisotropic nanomaterials have been used to improve the efficiency of CO2 conversion into useful chemicals and fuels using a variety of processes such as photocatalysis, electrocatalysis, and thermocatalysis. More study is required to improve the usage of anisotropic nanomaterials for CO2 consumption and to scale up these technologies for industrial use. The unique properties of anisotropic nanomaterials, such as their high surface area, tunable morphology, and high activity, make them promising catalysts for CO2 utilization. This review article discusses briefly about various approaches towards the synthesis of anisotropic nanomaterials and their applications in CO2 utilization. The article also highlights the challenges and opportunities in this field and the future direction of research.